The buyout of prosiebensat.1 by KKR and permira – blockbuster or box office bomb? - Bungert, Jonas (2017)
This case study describes the buyout of ProSiebenSat.1 during the peak of the buyout boom in 2007. Against the backdrop of the global financial crisis, it illustrates how the financial sponsors pursued an internationalization strategy by combining ProSiebenSat.1 with another portfolio com-pany which eventually led to the financial distress of ProSiebenSat.1. The case study addresses the unique features of the investment thesis, namely the target characteristics as well as transaction structure and how the investors adjusted their initial investment thesis to encounter the issues faced. The deal is an example of many unsuccessful buyouts which happened during the financial crisis.